Racial and ethnic disparities in preterm birth: a mediation analysis incorporating mixtures of polybrominated diphenyl ethers - Wang, Zifan; Zhang, Cuilin; Williams, Paige L.; Bellavia, Andrea; Wylie, Blair J.; Kannan, Kurunthachalam; Bloom, Michael S.; Hunt, Kelly J.; James-Todd, Tamarra (Frontiers in Reproductive Health, 2024)
Background: Racial and ethnic disparities persist in preterm birth (PTB) and gestational age (GA) at delivery in the US. It remains unclear whether environmental chemicals exposure might contribute to these disparities. Objectives: We applied recent methodologies incorporating environmental mixtures as mediators in causal mediation analysis to examine whether racial and ethnic disparities in GA at delivery and PTB may be partially explained by exposures to polybrominated diphenyl ethers (PBDEs), a class of chemicals used as flame retardants in the US. Methods: Data from a multi-racial/ethnic US cohort of 2008 individuals with low-risk singleton pregnancies were utilized, with plasma PBDE concentrations measured during early pregnancy. We performed mediation analyses incorporating three forms of mediator(s): 1) reducing all PBDEs to a weighted index, 2) selecting a PBDE congener, or 3) including all congeners simultaneously as multiple mediators, to evaluate whether PBDEs may contribute to the racial and ethnic disparities in PTB and GA at delivery, adjusted for potential confounders. Results: Among the 2008 participants, 552 self-identified as non-Hispanic White, 504 self-identified as non-Hispanic Black, 568 self-identified as Hispanic, and 384 self-identified as Asian/Pacific Islander. Non-Hispanic Black individuals had the highest mean ∑PBDEs, the shortest mean GA at delivery, and the highest rate of PTB. Overall, the difference in GA at delivery comparing non-Hispanic Black to non-Hispanic White women was -0.30 (95% CI: -0.54, -0.05) weeks. This disparity reduced to -0.23 (95% CI: -0.49, 0.02) and -0.18 (95% CI: -0.46, 0.10) weeks if fixing everyone’s weighted index of PBDEs to the median and 25th percentile levels, respectively. The proportion of disparity mediated by the weighted index of PBDEs was 11.8%. No statistically significant mediation was found for PTB, other forms of mediator(s), or other racial and ethnic groups. Conclusion: PBDE mixtures may partially mediate the Black vs. White disparity in GA at delivery. While further validations are needed, lowering the PBDEs at the population level might help reduce this disparity.